ROLE OF THE ORGANIZATIONAL DESIGN IN THE COMPANY’S SUCCESS - Eka Chokheli (European Scientific Journal, ESJ, 2015)
Organizational structure is necessary for the organizational activity of any business company. Expediently selected structure fully responding the existing challenges and meeting the requirements of the strategic view is the guarantee for the company’s success. The goal of the article is to evaluate the role of the organizational structure, identify the problems associated with the organization structure of the companies and ways of development. The theoretical analysis used in the study is based on the works of the worldly famous scientists, and the practical analysis is based on the qualitative study of the selected companies working in the industrial branch of Georgia. Questionnaires, interviews and information sources of companies are used for this purpose. The study uses graphical methods and methods of grouping, comparison and analysis. The results of the study revealed the factors hampering a company to efficiently use the resources and give the recommendations helping the companies to improve their business and competitiveness and strengthen their positions on the market.